PARALLEL CORPUS IN THE PRACTICE OF TRANSLATING SOCIAL TEXTS - Abdullaeva, Zamira; Haydarova, Marhamat; Shikhnazarova, Guzal (SAMBHRAM XABARNOMASI, 2024)
Annotation In this article, corpus linguistics, corpus and its parallel corpus, a word about ideas, its structure, corpus types, token, lemma, stemming. Today, the theoretical and practical significance of the corpus is Uzbek in linguistics, in a wider study of the existing possibilities of the language, in linguistics identifying problematic aspects, creating electronic dictionaries, learning the language in improving the efficiency of using modern information technologies, in the language in dealing with issues such as automatic translation, search and computer analysis, of language shows that there is a need to build a corps in special fields. Key words: corpus, corpus linguistics, parallel corpus, translation corpus.